Pediatric Intestinal Transplant Listing Criteria – A Call for a Change in the New Era of Intestinal Failure Outcomes. Issue 6 (23rd March 2015) - Burghardt, K. M.; Wales, P. W.; de Silva, N.; Stephens, D.; Yap, J.; Grant, D.; Avitzur, Y.
<x xml:space="preserve">Abstract</x> Current listing indications used for intestinal transplantation (IT) were proposed in 2001. We undertook the present single center study to see if these criteria are still valid. The 2001 criteria (advanced cholestasis, loss of >50% central venous catheter (CVC) sites, ≥2 sepsis/year, ultrashort bowel) were compared in children with intestinal failure in old era—1998–2005 (N = 99) to current era—2006–2012 (N = 91) to predict the need for IT using sensitivity, specificity, NPV and PPV. Two 2001 criteria had poorer predictive value in the current era: Advanced cholestasis (PPV 64% old vs. 40% current era; sensitivity 84% vs. 65%, respectively) and ultrashort bowel (PPV 100% old vs. 9% current era; sensitivity 10% vs. 4%, respectively). Three newly proposed criteria had high predictive value: ≥2 ICU admissions (p = 0.0001, OR 23.6, 95% CI 2.7–209.8), persistent bilirubin >75 mmol/L despite lipid strategies (p = 0.0005, OR 24.0, 95% CI 3.2–177.4), and loss of ≥3 CVC sites (p = 0.0003, OR 33.3, 95% CI 18.8–54.0). There was 98% probability of needing IT when two of these new criteria were present. The 2001 IT criteria have limited predictive ability in the current era and should be revised. A multicenter study is required to validate the findings of this single center experience.